2009
DOI: 10.1007/s11136-009-9506-y
|View full text |Cite
|
Sign up to set email alerts
|

Readability estimates for commonly used health-related quality of life surveys

Abstract: Purpose To estimate readability of seven commonly used health-related quality of life instruments: SF-36, HUI, EQ-5D, QWB-SA, HALex, Minnesota Living with Heart Failure Questionnaire (MLHFQ), and the NEI-VFQ-25. Methods The Flesch-Kincaid (F-K) and Flesch Reading Ease (FRE) formulae were used to estimate readability for every item in each measure. Results The percentage of items that require more than 5 years of formal schooling according to F-K was 50 for the EQ-5D, 53 for the SF-36, 80 for the VFQ-25, 85 for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 39 publications
(35 reference statements)
0
38
0
2
Order By: Relevance
“…35 Changes in process, work flow and information systems are likely to be needed to ensure that the assessments are done regularly and to inform clinical decisions; 36 this requires technical support to set up and maintain the system (paper or electronic), help and explanations for individual patients, staff education and senior management backing. 37 Short questionnaires (parsimony) tend to provide higher participation rates, reduced respondent resistance 38 Readability is selfevidently important, yet Paz and colleagues 39 found that all commonly used instruments have many items with readability levels below the threshold recommended for documents to be used by vulnerable people of a readability grade score of 5.0 or less and a reading ease score of over 80. 40 The howRu form has a grade score of 1.8 and an ease score of 89.…”
Section: Implications For Practicementioning
confidence: 99%
“…35 Changes in process, work flow and information systems are likely to be needed to ensure that the assessments are done regularly and to inform clinical decisions; 36 this requires technical support to set up and maintain the system (paper or electronic), help and explanations for individual patients, staff education and senior management backing. 37 Short questionnaires (parsimony) tend to provide higher participation rates, reduced respondent resistance 38 Readability is selfevidently important, yet Paz and colleagues 39 found that all commonly used instruments have many items with readability levels below the threshold recommended for documents to be used by vulnerable people of a readability grade score of 5.0 or less and a reading ease score of over 80. 40 The howRu form has a grade score of 1.8 and an ease score of 89.…”
Section: Implications For Practicementioning
confidence: 99%
“…This is also important because patients are concentrated amongst the most vulnerable, disadvantaged and deprived sectors of society. Paz et al 10 suggested a criterion of five years of schooling as appropriate for health surveys, and found that none of seven commonly used surveys that they tested, including EQ-5D, achieved this. The readability grade, which approximates to years of schooling needed, is 2.6 for howRU, compared with 6.0 for EQ-5D.…”
Section: Discussionmentioning
confidence: 99%
“…Although many readability formulae are available, Flesch Reading Ease Score (FRES) is a popular, tested and reliable tool for readability testing (Rameezdeen & Rajapakse, 2007). FRES is consistent and highly associated with other indices (Paz et al 2009). Therefore, FRES is considered to be suitable for assessing the readability levels of modified clauses against the standard conditions in this research.…”
Section: Methodsmentioning
confidence: 99%